COLOR REVOLUTIONS AS A THREAT TO SECURITY OF THE RUSSIAN FEDERATION. THE ANALYSIS OF RUSSIAN PERSPECTIVE - Minkina, Mirosław; Kaszuba, Malina (Torun International Studies, 2021)
The article attempts to analyze and assess Russian perspectives of color revolutions as a threat to national security. Then the article focuses on the discussion of Russian concepts for countering color revolutions. The authors formulated the main research problem as the following question: What are the social movements, known as color revolutions, for the Russian Federation?; and formulates the following hypothesis: Color revolutions are recognized by the Russian authorities as social engineering inspired by the West, the aim of which is to overthrow the constitutional order of Russia and the states of the post-Soviet space to draw them into the sphere of influence of Euro-Atlantic structures. Color revolutions are considered a serious threat to national security by the Russian ruling elites. The first reason is the fear that the Russians, following the successful revolutions within the post-Soviet area, will themselves want to change the political system. The second is the loss of Russian influence in the countries of the former USSR. Color revolutions in the post-Soviet area have usually resulted in the emergence of pro-Western governments reluctant to Moscow. This, in turn, prevents the Russian ruling elites from rebuilding the empire.